Parvalbumin Interneuron Activation-Dependent Adult Hippocampal Neurogenesis Is Required for Treadmill Running to Reverse Schizophrenia-Like Phenotypes - Yi, Yandong; Song, Yuanlong; Lu, Yisheng (Frontiers in Cell and Developmental Biology, 2020)
Disruption of adult hippocampal neurogenesis is associated with schizophrenia (SCZ). Although physical exercise can alleviate symptoms of SCZ patients, the mechanisms are still unclear. In this study, we found treadmill running effectively rescued the SCZ-related behavior phenotypes and promoted adult hippocampal neurogenesis in MK801 induced SCZ animal model, both the number and dendrite complexity of new born neurons were increased. Parvalbumin (PV) positive GABAergic interneurons in dentate gyrus (DG) was also increased after treadmill running. Genetic ablation of PV interneurons caused aberrant neurogenesis in DG, and abolished the rescue effect of treadmill running for SCZ phenotypes; however, activation of PV+ neurons in DG by chemogenetic technology alleviated SCZ-related behavior phenotypes and improved neurogenesis, suggesting exercise therapeutic effect of SCZ phenotypes depend on PV interneuron-related positive modulation of adult neurogenesis in DG. However, SCZ behavior phenotypes and adult neurogenesis in DG still could be reversed by exercise after specific knockout SCZ related gene ErbB4 in PV interneurons to reduce their GABA release, suggesting activation of PV interneurons in DG is enough for treadmill running to reverse SCZ phenotypes.